2011
DOI: 10.5344/ajev.2011.11029
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Shoot and Cluster Thinning on Yield, Fruit Composition, and Wine Quality of Corot noir

Abstract: The treatments had variable impacts on wine anthocyanin, berry skin tannin, berry seed tannin, and wine tannin depending on year. Wine tannin (42 to 64 mg/L) and tannin extractability (5 to 6%) were both very low compared to values typically observed in red wines produced from V. vinifera. Using a two-alternative forced choice test, panelists reported ST+CL wines were fruitier than the control and ST wines and that ST wines were less fruity than the control in both years. An economic analysis indicated that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
43
0
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 25 publications
5
43
0
11
Order By: Relevance
“…The yield was slightly reduced in 2011 as a result of the excessive vigour of the vines in 2010, resulting in poor floral bud initiation, similar to the report by Sun et al (2012). The excessive vigour was the consequence of excessive rainfall during the vegetation period.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…The yield was slightly reduced in 2011 as a result of the excessive vigour of the vines in 2010, resulting in poor floral bud initiation, similar to the report by Sun et al (2012). The excessive vigour was the consequence of excessive rainfall during the vegetation period.…”
Section: Resultssupporting
confidence: 66%
“…The noteworthy yield reductions in both cultivars must be taken into account when applying similar treatments, because of significant economic implications for vineyard operators (King et al 2012). The reduced yield per vine achieved by cluster thinning has been previously reported (Reynolds et al 1995;Miller & Howell 1998;Keller et al 2005;Dami et al 2006;Di Profio et al 2011a;King et al 2012;Sun et al 2012), as well as concomitant increases in cluster weight (Reynolds et al 1995;Dami et al 2006;King et al 2012;Sun et al 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are in agreement with those of Di Profio et al (2011), when studying the Cabernet Sauvignon, Merlot, and Cabernet Franc cultivars in the USA. These results can be explained by the fact that anthocyanin content is highly dependent on the levels of solar radiation, both in the vegetative canopy and directly in the clusters (Sun et al, 2012).…”
Section: Resultsmentioning
confidence: 96%
“…In previous studies, Moreno et al (2014) also observed that leaf removal resulted in greater accumulation of phenolic compounds, whereas Tardaguila et al (2010) and Risco et al (2014) found that early leaf removal caused an increase in polyphenol content. It has been suggested that the biosynthesis of polyphenols is light dependent, favoring their accumulation (Sun et al, 2012).…”
Section: Resultsmentioning
confidence: 99%